Short-Term Outcome Predictors in Patients With Primary Adhesive Capsulitis Treated With Ultrasound-Guided Hydrodilatation With Corticosteroids. (August 2020) - Yang, Chen-Ya; Fu, Li-Heng; Lee, Chao-Chung; Wang, Kevin A.; Chou, Chen-Liang; Wang, Jia-Chi
Abstract : Objective: Glenohumeral joint hydrodilatation with corticosteroids has been proposed as an effective secondary therapeutic procedure for primary adhesive capsulitis. However, little is known about which subgroup of patients would benefit from this procedure. This study aimed to identify covariates associated with improved prognosis in patients receiving ultrasound-guided hydrodilatation with corticosteroid injection. Design: This was a cohort study. Data on baseline demographic characteristics, disease status, past medical conditions, and initial ultrasonographic findings were collected. Linear and logistic regression analyses were performed to determine the prognostic factors associated with better clinical outcomes. Results: Fifty-three patients (54 shoulders) were included. Linear regression analysis showed that coracohumeral ligament thickness of less than 3 mm, use of analgesics before hydrodilatation, and female sex were associated with good improvement in the Shoulder Pain and Disability Index score. Multivariate logistic regression analysis showed that coracohumeral ligament thickness of less than 3 mm on ultrasound was associated with a strong tendency ( P = 0.054) of reaching the minimal detectable change. In addition, capsule rupture did not play a role in determining the clinical efficacy of hydrodilatation. Conclusions: In patients with primary adhesive capsulitis, coracohumeral ligament thickness of less than 3 mm is correlated with greater short-term improvement in the Shoulder Pain and Disability Index score after ultrasound-guided hydrodilatation with steroid injection is performed. Abstract : Supplemental digital content is available in the text.